PENGARUH KECEPATAN SPINDLE DAN KEDALAMAN PEMAKANAN PROSES CNC FRAIS TERHADAP KEKASARAN DAN KEKERASAN PERMUKAAN REMELTING BLOK SILINDER (Fakultas Teknik, Universitas Negeri Semarang, 2019)
This study aims to examine the effect of spindle speed and depth of cut on roughness of surface of remelting cylinder block on CNC frais process. To reachÂ the objective its various spindle speed of 1150 rpm, 1350 rpm, and 1600 rpm, while its various depth of cut of 0,25 mm, 0,5 mm, and 0,75 mm. The roughness of the sample measure using Surface Roughness Tester Surfcorder SE 1700 Flowler. Based on this research, spindle speed and depth of cut affect roughness of surface material. High spindle speeds and low depth of cut produced low roughness of surface material. The result lowest roughness that on spindle speed 1600 rpm and depth of cut 0,25 mm is 2,347 Âµm. The selection of these parameters is also adjusted to the type of tool and material used.Â